Activity of upper body muscles during bowing and prostration tasks in healthy subjects - Safee, M.K.M.; Wan Abas, Wan Abu Bakar; Abu Osman, Noor Azuan; Ibrahim, Fatimah (2011)
This paper investigate the activity of the neck extensors (NE), sternocleidomastoideus (SCM), trapezius (TRP), deltoid (DT), biceps brachii (BB), triceps brachii (TB), rectus abdominal (RA), and erector spine (ES) muscles in healthy subjects during bowing and prostration using surface electromyography (EMG). A group of student aged between 23 to 28 years voluntarily participated in this study. The subjects were asked to perform two types of flexion positions, namely bowing (90 o forward flexion with the hands on the respective knees) and prostration (flexion with the palms of the hands and the forehead flat on the floor). The motion signals of the muscles were recorded. The finding indicated that during the bowing, there was contraction of the NE, DT, TB, and RA muscles while the muscle relaxation was found in the SCM, TRP, BB, and ES. During prostration, there was contraction at the SCM, DT, TB, and RA but muscle relaxation was found at the NE, TRP, BB, and ES. For the muscles that showed electrical activity in both the postures, the Wilcoxon Rank Sum Test showed a statistically no significant difference between bowing and prostration only for DT (p = 0.534) and but statistically significant difference for RA and TB (p<0.05). The muscle relaxation that existed at the ES showed no significant difference between bowing and prostrating (Wilcoxon Rank Sum Test, p = 0.075). This study indicates the effects of bowing and prostration on the biomechanical response of the human muscles. Muscle contraction and relaxation that occur, show an agonist-antagonist response which is good for exercise and strengthening programmers. These two movements are involved in the Muslim’s prayer, called the salat. Hence, the current experiment can be taken as a pilot study on the biomechanical response of the human muscles during one’s act of performing the salat.